Included but Unheard: Communication, Trust, and Financial Exclusion in Rural Indonesia - Franssisca Xaveria; Kevin Sanly Putera; Muhammad Fasha Rouf (Universitas Multimedia Nusantara, 2026)
Financial inclusion in emerging economies depends not only on the expansion of financial services but on the communicative processes through which communities engage with those services meaningfully. In Indonesia, rural populations continue to face barriers to formal financial participation despite measurable improvements in financial literacy, a divergence that points to a failure of participatory communication rather than information provision alone. This study examines BRILink, Bank Rakyat Indonesia's branchless banking programme, as a communication system through which financial inclusion is constructed, negotiated, and constrained in Pujon Village, East Java. Using a qualitative approach, in-depth interviews and field observations were conducted with BRILink agents and customers. Analysis through a Communication for Development (C4D) lens, drawing on van de Fliert's participatory communication framework and Dutta's Culture-Centered Approach, produced three themes: agent-mediated trust and the social construction of financial inclusion; communicative dilemmas in agent-customer relationships; and institutional communication gaps driving agent self-directed learning. Findings reveal that BRILink succeeds as a service delivery mechanism but reproduces communicative exclusion by treating agents as transaction processors rather than communication intermediaries and by structuring community relationships as unidirectional dissemination rather than dialogue. We argue that sustainable financial inclusion requires institutions to invest in participatory communication as its foundation.